Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
https://search.libraries.emory.edu/catalog/990005217790302486
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

L'identité féminine : biologie ou conditionnement social? - Irigaray, Luce (Femmes : moitié de la terre, moitié du pouvoir, 1994)
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; europe; fem1000; france; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (Rowman & Littlefield, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Section: xx, 236 pages
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques

"Chapitre I".De l'assujettissement des femmes. - Mill, John Stuart (De l'assujettissement des femmes, 1992)
Première édition 1867
Keywords: 1800-1899; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; fem1000; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

De l'assujettissement des femmes. - Mill, John Stuart (Avatar, 1992)
L´écrivain britannique John Stuart Mill était l´un des premiers écrivains masculins à se positionner pour l´égalité des sexes et à défendre la libération des femmes. Il se pencha sur la liberté économique des femmes et était de l´avis que le rôle d´une femme dans le mariage devait évoluer. Le livre « De l’assujettissement des femmes » est un classique de la littérature féministe. Le philosophe et politicien britannique John Stuart Mill (1806+1873) est un des penseurs libéraux les plus importants du 19e siècle. Il est particulièrement connu pour ses théories d´utilitarisme. Il s´est occupé de divers sujets politiques et philosophiques, dont les concepts de liberté et d´égalité des sexes.
Première édition 1867
Keywords: 1800-1899; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; fem1000; phi4336; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; femmes*; identité sexuelle; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; états-unis; études culturelles

Traité de la morale et de la politique 1693: la Liberté - Suchon, Gabrielle (Des Femmes-Antoinette Fouque, 1988)
« Vous prendrez garde, mon lecteur, qu'encore que la Morale et la Politique ne soient pas traitées en ce livre selon la méthode ordinaire des Philosophes et des Théoriciens, l'on peut néanmoins y reconnaître les principales matières de ces deux grands sujets. » Voici présenté par Gabrielle Suchon elle-même, son Traité de Morale et de Politique, publié à Lyon en 1693. Le présent ouvrage est la réédition de la première partie, la Liberté, cette « qualité savoureuse ». Avec Gabrielle Suchon, le sexe - ou, comme elle l'écrit : le Sexe - fait son entrée en philosophie. Sous sa plume, la liberté perd la figure abstraite d'un concept métaphysique pour se transformer en une question brûlante, née d'une douloureuse privation : quelle liberté pour le Sexe ? Comme le souligne Séverine Auffret, Gabrielle Suchon ne se situe pourtant pas dans une lignée féministe. Nourrie de Platon, d'Aristote et des Écritures, c'est bien dans le champ philosophique qu'elle se meut et qu'elle vient « fêter » quelque chose. Agrégée de philosophie, Séverine Auffret a entrepris de faire éditer l'oeuvre de Gabrielle Suchon (1632-1703).
Donné en lecture cours FEM1000: p.30-40;85-92;207-215
Keywords: 1600-1699; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; philosophie; premier cycle; périodes historiques; régions géographiques; savoirs; sciences humaines; systèmes d'oppressions

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Section: xvi, 175 pages ; 22 cm
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; épistémologie

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme

Histoire de la sexualité I. La volonté de savoir - Foucault, Michel (Gallimard, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."– Site de l'éditeur.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; his4860; histoire; histoire de la sexualité; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques

L’hypothèse répressive - Foucault, Michel (Histoire de la sexualité. 1. La volonté de savoir, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."– Site de l'éditeur.
SEX1183-Chapitre 2. L’hypothèse répressive; pages 25 à 49
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; histoire; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques